Plan de mejoramiento para el fortalecimiento de la internacionalización curricular en las Especializaciones Médico Quirúrgicas de la Escuela de Medicina y Ciencias de la Salud de la Universidad del Rosario (2025)
This paper investigates the curricular internationalization of surgical and medical specializations at Universidad del Rosario. Due to the nature of these programs, they require specific strategies for both professors and students.